2013
DOI: 10.1016/j.cub.2013.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Translational Control and Protein Homeostasis during Severe Heat Stress

Abstract: Chaperone-driven protein disaggregation directly coordinates timing of translation reinitiation with protein folding capacity during cellular protein quality surveillance, enabling efficient protein homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
242
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(266 citation statements)
references
References 43 publications
21
242
3
Order By: Relevance
“…Indeed, work in yeast and Drosophila spp. has concluded that chaperones are associated with stress granules and are necessary for the resumption of translation after severe heat stress (Cherkasov et al, 2013). While our experiments point to a clear interaction between sHSPs, specific translation factors, and HSP101, we also observed distinct cytosolic foci of CI and CII sHSPs that did not colocalize with either the identified translation factors or HSP101.…”
Section: Discussioncontrasting
confidence: 67%
“…Indeed, work in yeast and Drosophila spp. has concluded that chaperones are associated with stress granules and are necessary for the resumption of translation after severe heat stress (Cherkasov et al, 2013). While our experiments point to a clear interaction between sHSPs, specific translation factors, and HSP101, we also observed distinct cytosolic foci of CI and CII sHSPs that did not colocalize with either the identified translation factors or HSP101.…”
Section: Discussioncontrasting
confidence: 67%
“…Third, we do not observe an HSP104-dependent recovery (Supplemental Fig. S1), as in the case with heat stress granules (Cherkasov et al 2013). It is possible that in the absence of HSP70/40 proteins, distinct protein aggregates also form, and might even merge with stress granules under some conditions (Buchan et al 2013).…”
Section: Discussionmentioning
confidence: 52%
“…Several observations argue that the structures we observe are bona fide stress granules, as opposed to "heat stress granules" (Cherkasov et al 2013). First, Pab1-GFP foci in this work are cycloheximide sensitive and contain additional SG markers (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Various heat shock proteins (HSPs) localize to, and affect, disassembly of stress granules in humans, flies, and yeast. 24,33,74,78 An appealing model 78 is that when cellular stress leads to accumulation of unfolded proteins, titration of HSPs would cause slower stress granule disassembly and trapping of mRNAs in nontranslating states, thus helping cells conserve resources. As HSPs become available again either via increased synthesis, or from having dealt with other unfolded proteins, stress granules could once more be disassembled.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%